2014
DOI: 10.1016/j.cellsig.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A novel insulin receptor-signaling platform and its link to insulin resistance and type 2 diabetes

Abstract: Insulin-induced insulin receptor (IR) tyrosine kinase activation and insulin cell survival responses have been reported to be under the regulation of a membrane associated mammalian neuraminidase-1 (Neu1). The molecular mechanism(s) behind this process is unknown. Here, we uncover a novel Neu1 and matrix metalloproteinase-9 (MMP-9) cross-talk in alliance with neuromedin B G-protein coupled receptor (GPCR), which is essential for insulin-induced IR activation and cellular signaling. Neu1, MMP-9 and neuromedin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 93 publications
2
70
0
Order By: Relevance
“…It has also been shown that insulin can mediate increases in MMP9 via insulin receptor (IR) activation [148], which fits well within this molecular signaling platform for insulin-induced receptors [59]. The study has also shown that insulin can induce MMP9 upregulation via the mitogenic signaling pathways, and renders the PI3K-dependent signaling pathway unnecessary.…”
Section: Gpcr Signal Integration In Receptor Tyrosine Kinase Activationmentioning
confidence: 69%
See 2 more Smart Citations
“…It has also been shown that insulin can mediate increases in MMP9 via insulin receptor (IR) activation [148], which fits well within this molecular signaling platform for insulin-induced receptors [59]. The study has also shown that insulin can induce MMP9 upregulation via the mitogenic signaling pathways, and renders the PI3K-dependent signaling pathway unnecessary.…”
Section: Gpcr Signal Integration In Receptor Tyrosine Kinase Activationmentioning
confidence: 69%
“…It is noteworthy that we have reported a striking similarity with this novel receptor signaling platform for nerve growth factor (NGF) TrkA receptors [35], insulin [59, 60] and cell surface TOLL-like receptor (TLR)-4, [34, 6164] and intracellular TLR7 and TLR9 receptors [65], all of which require receptor dimerization and are regulated by Neu1. Pshezhetsky and Ashmarina [66] have recently summarized the emerging data demonstrating that Neu1, well known for its lysosomal catabolic function, is also localized to the cell surface and assumes the previously unrecognized role as a structural and functional modulator of cellular receptors.…”
Section: A Novel Egfr-signaling Platform and Its Targeted Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, adverse effects precipitated by increased fructose intake include negative effects on cardiovascular and kidney functions. Earlier studies reported that high sugar diet can lead to insulin resistance, while defects in the insulinsignaling pathway may be due to high fat diet [24]. In this study, HFD and HSD rats reproduced the changes in blood glucose, plasma triglyceride and cholesterol levels which may leads to insulin resistance and impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 57%
“…Insulin-stimulated tyrosine phosphorylation of IR β-subunit, which is correlated with full activation of the IR tyrosine kinase (14,15), did not change significantly in liver tissue between MI and control rats ( Figure 2A). By contrast, insulinstimulated tyrosine phosphorylation of IRS1 decreased by almost 70% more in MI rats than in controls ( Figure 2B).…”
Section: Impaired Insulin Signaling Pathways In Liver After MImentioning
confidence: 99%